Marathon County farmland preservation survey report, 2013 - Hadley, Shelly; Janke, James; Trechter, David (My University, 2013)
The purpose of this study was to gather opinions with respect to farmland preservation and agricultural issues in Marathon County. County officials identified two populations to include in the survey: agricultural stakeholders and the general public. The questionnaires for these two populations were very similar. The primary difference was the addition of several questions on the agriculture stakeholder version.
Keywords: Farmland preservation; Farmers; Marathon County (Wis.); Public opinion survey; Marathon County, Wisconsin